Penerapan Model Certainty Factor Untuk Mendeteksi Gejala Kanker Mulut Rahim - Mariana, Novita; Gernowo, Rahmat; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
An expert system is a system that seeks to adopt human expertise so that computers can do things that can be done by an expert to solve specific problems. Experts in this case is an expert in the field to address the problem under on detecting cervical cancer. Cervical cancer is a disease that is very afraid of all women because it attacks the reproductive organs caused by the virus Human Papilloma Virus (HPV). The system is made to detect cervical cancer using the certainty factor with a forward chaining inference engine. Certainty factor method used in cervical cancer detection system to give certainty to the disease. As a result of this information system is to provide information regarding the statement of cervical cancer and cancer treatment solution according to the stage. Â  Kata kunci : Certainty Factor; Forward Chaining; Kanker Mulut Rahim